Peire Vidal, "Pus ubert ai mon ric thesaur" (BdT 364.38) - Fortunata Latella (Lecturae Tropatorum, 2015)
The sirventes-canso "Pus ubert ai mon ric tezaur" by Peire Vidal is characterized, especially in the central part (coblas II-VII), by a particularly creative use of language which culminates in verbal invention; although commentators have grasped the allusive and etymological value of the toponymic creations in the text, the meaning hidden under these euphemisms has so far not been explained. The analysis carried out here seeks to highlight this secondary level of reading, that reveals a distinctly erotic and sometimes indecent scenario, which neverthless always remains on a playful and humorous level.